A Modular Simulation Framework for Spatial and Temporal Task Mapping onto Multi-Processor SoC Platforms - Kempf, Torsten; Doerper, Malte; Leupers, R.; Ascheid, G.; Meyr, H.; Kogel, Tim; Vanthournout, Bart (Design, Automation and Test in Europe, 2005)
Heterogeneous Multi-Processor SoC platforms bear the potential to optimize conflicting performance, flexibility and energy efficiency constraints as imposed by demanding signal processing and networking applications. However, in order to take advantage of the available processing and communication resources, an optimal mapping of the application tasks onto the platform resources is of crucial importance. In this paper, we propose a SystemC-based simulation framework, which enables the quantitative evaluation of application-to-platform mappings by means of an executable performance model. Key element of our approach is a configurable event-driven Virtual Processing Unit to capture the timing behavior of multi-processor/multi-threaded MP-SoC platforms. The framework features an XML-based declarative construction mechanism of the performance model to significantly accelerate the navigation in large design spaces. The capabilities of the proposed framework in terms of design space exploration is presented by a case study of a commercially available MP-SoC platform for networking applications. Focussing on the application to architecture mapping, our introduced framework highlights the potential for optimization of an efficient design space exploration environment.